Directional northern element in the flora of vascular plants of Poland - Zając, Maria; Zając, Adam (Biodiversity: Research and Conservation, 2011)
The directional element is a local determinant of spatial diversity of flora of a given country, within widely understood geographical elements. In Poland, a country situated in the middle of Europe, most species belong to the transitional element (with no range limit in our country). Besides the transitional element, the directional northern element (with its southern limit in Poland) is present. It can be divided into two distinct groups: species that have their absolute southern range limit in Poland and those that have both southern and northern limits with a significant disjunction in Central Poland. Although they are two different groups, they will be discussed within the combined study. The first one constitutes 1.9% of the directional element, the second one 1.3%. As far as general ranges are concerned, Circumboreal and Eurosiberian species prevail in the first group, with a significant share of the taxa of geographical connective element. European-temperate taxa are the most numerous in the second group. The two above-mentioned groups will also be distinguished by their species belonging to the higher syntaxonomical units. Such a small share of the northern element in the flora of Poland confirms that our country belongs to the Central European Province, where the North-European element is, to a large extent, a relict of the earlier periods of the Holocene.